Redistributive effects of non-contributory pension schemes in the European Union - Francesco Cellino; Flavia Coda Moscarola; Francesco Figari (University of Essex, Institute for Social and Economic Research (ISER), 2025)
This paper investigates the role of non-contributory pension schemes in alleviating poverty among the elderly in the European Union. Non-contributory pensions, which are not linked to previous earnings or contributions, are a key element of public pension systems aimed at reducing poverty in old age. Using EUROMOD, the European tax-benefit microsimulation model, this study covers pension schemes in place in 2021 in most EU countries. Our findings show that non-contributory pensions are a significant component of older individuals' income in nearly all EU countries, particularly in nations like Denmark, Ireland, and the Netherlands, where universal basic pensions exist. In most other countries, these pensions are targeted at the poorest elderly. Our simulations estimate that abolishing non-contributory pensions would lead to a heterogeneous increase in elderly poverty rates across countries up to 64 percentage points. We also find that countries with more generous non-contributory schemes tend to have stronger general social assistance instruments.
Keywords: H55; I32; I38; 330; pension systems; non-contributory pensions; old-age poverty; EUROMOD